(untitled) (Journal of Applied Business and Technology, 2025)
Department of Industry, Trade, Cooperatives and SMEs (DITCS) of Riau has an important role in supporting 631,347 groups of Micro, Small and Medium Enterprises (MSMEs) engaged in various fields such as handicrafts, batik, songket, and food and beverages. Many MSME merchants still market their products traditionally through the neighborhood and word of mouth, while online marketing faces a big challenge because they have to compete with well-known brands, making them difficult to develop and grow their business. To overcome these problems, an Android-based application “LaKu” was developed that aims to help MSME merchants in expanding their marketing reach and increasing their competitiveness in Riau. The development of this application uses the Extreme Programming (XP) method which consists of four main steps: Planning, Design, Code, and Testing. The development results show that the “LaKu” application can be an effective digital marketing platform, helping MSMEs in promoting products more widely without having to compete directly with big brands. With this application, MSMEs are able to increase competitiveness and contribute to local economic growth in Riau Province.